The World Book encyclopedia of people and places. - World Book, Inc. (Chicago World Book, 2011)
"A 7-volume illustrated, alphabetically arranged set that presents profiles of individual nations and other political/geographical units, including an overview of history, geography, economy, people, culture, and government for each. Includes a history of the settlement of each world region based on archaeological findings; a cumulative index; and Web resources"--Provided by publisher.
v. 1. A-B, Afghanistan to Burundi -- v. 2. C-F, Cambodia to French Polynesia -- v. 3. G-J, Gabon to Jordan -- v. 4. K-N, Kazakhstan to Norway -- v. 5. O-S, Oman to Syria -- v. 6. T-Z, Tahiti to Zimbabwe -- v. 7. People on the move settling the world's regions.
Keywords: Encyclopedias and dictionaries; Geography -- Encyclopedias